The Application of CAPM As A Basis For Determining The Return Level, Risk To Determine The Efficient Stock Group On Companies Listed On Indonesia Stock Exchange - Anastasya Dyah Puspita; Muhaimin Dimyati; Ratih Rachmawati (ABM: International Journal of Administration, Business and Management, 2019)
Along with the increasing interest of the public to invest in the capital market, the analytical ability of an investor is needed in determining investment options. CAPM is a balance model that describes the relationship between risk and returns where risk is measured using beta. This research was conducted on food and baverage company period 2013-2016. The analytical method used is descriptive statistics. The results showed that there was a positive or linear relationship between expected rate of return and systematic risk. There are 4 shares with negative individual return. From 14 companies, there are 8 shares that include the efficient stock groups: AISA, CEKA, INDF, PSDN, SKBM, SKLT, STTP, ULTJ. 6 shares that include inefficient stock groups are: ALTO, DLTA, ICBP, MLBI, MYOR, ROTI. An efficient share is a stock with an individual rate of return higher than the expected rate of return The investment decision taken is to buy the stock efficiently (undervalued) and hold it and then sell back when the prices rise. For the inefficien shares (overvalue) is to sell the stock before the price goes down. Keywords: CAPM, return, risk, beta